Cosmopolitan conceptions : IVF sojourns in global Dubai - Inhorn, Marcia C., 1957- (Duke University Press, 2015)
Marcia C. Inhorn's ethnography of international travelers seeking in vitro fertilization treatment in the global IVF hub of Dubai shows that infertile couples, or ""reprotravelers, "" leave their countries because IVF treatment is not safe, affordable, legal or effective. Inhorn opens a window into the painful, frustrating, and expensive world of infertility.